Effects of Transfusion on Free Flap Survival: Searching for an Optimal Hemoglobin Threshold for Transfusion - Kim, Min Ji; Woo, Kyong-Je; Park, Bo Young; Kang, So Ra (Journal of Reconstructive Microsurgery, 2018)
Background Microsurgical free tissue transfer is a popular technique nowadays. Because of its considerably exquisite procedure, various risk factors can affect surgical outcome. However, current key practices, especially those in blood transfusion, are in contention due to the lack of enough evidence. Therefore, the objective of this study was to investigate the impact of perioperative blood transfusion on microsurgical complication.Methods Data of a total of 168 patients who underwent microvascular free tissue transfer from 2013 through 2016 were retrospectively reviewed. Age, comorbidity, anatomical surgical site, preoperative and postoperative lowest hemoglobin (Hb) level, estimated blood volume loss, and final clinical flap outcome were compared between patients with and without transfusion treatment. Factors with a significance of p < 0.05 in univariate analysis were included in the multivariate logistic regression model to identify independent risk factors.Results Of 168 patients, 72 (43%) were in the transfusion group. Cross analysis statistics showed that flap failure in the transfusion group was 3.6 times higher (p = 0.018) than that in the control group. Multivariable analysis revealed that age (p = 0.083) and perioperative lowest Hb level (p = 0.021) remained as significant predictors of flap failure. Receiver-operating characteristic curve analysis showed that the appropriate lower limit of transfusion commencement of Hb was 8.75 g/dL (area under the curve: 0.721).Conclusion A transfusion during perioperative period of free flap did not increase its failure rate. Rather than appropriate transfusion strategy, perioperative lowest Hb level, and age were significant predictors of flap failure. Therefore, transfusion can be confidently used in patients who undergo free flap without any hesitation. Results of this study provide practical evidence of performing perioperative transfusion for free tissue transfer patients.
Keywords: transfusion; free flap; flap survival; perioperative management; flap reconstruction